Simulation Aided Development of Alternatives for Improved Maintenance Network - Abdul Rahman, Azrul Azwan; Bilge, Pinar; Seliger, Günther (2011)
The success of organizations operating in complex environments depends on how well their value chain can adapt to disruptions caused by unanticipated events. Building this resilience requires the capability to identify uncertainties and modelling their impact on operations. To effectively achieve this is very difficult. Thus, increasing resilience in maintenance and repair networks calls for an adequate approach to address uncertainties. It is necessary to consider the maintenance activities within and outside the company and those affecting all supplier partners of equipment. This paper presents a comprehensive analysis, a potential approach to model their impact and alternatives to increase the flexibility of the network to ensure profitability and continuity.